RANCANG DESAIN ALAT PENGAYAK MODIFIED CASSAVA FLOUR (MOCAF) BERDASARKAN ANALISIS KEBUTUHAN, MORFOLOGI DAN TEKNIK - Slamet Sulistiadi; Fenny Aprilliani; Anri Kurniawan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Modified Cassava Flour (MOCAF) which has been produced by small industries has a particle size that is not yet the Indonesian National Standard (SNI), so the quality needs to be improved using a sieving machine. The objectives of this study are 1) to analyze the design requirements of the sieving machine 2) to determine the design concept 3) to analyze the technique 4) to design the sieving device in the engineering drawing. The method used in this research is observation, interview and French design method. Based on the results of the needs analysis, it was found that the design concept of the MOCAF sieve tool that uses an electric motor, is easy to operate, is in accordance with the production capacity, has an SNI size mesh and the material used is affordable. The results of the morphological analysis show that the design concept that can be developed is the design concept 1. The results of the technical analysis show that the linear velocity of the belt is 5.58 m / s and the tensile stress at T1 is 0.23 MPa. The dimensions obtained based on the design results are 5 cm pulley length, 99 x 59 x 10 cm mesh dimension, 100 mesh size and 108 x 80 x 95 cm machine frame dimensions. Keywords: analysis, design, MOCAF, morphology, sieving